Skiers individual respiratory system characteristics depending on the physical condition - G. G. Erofeev (Спортивная медицина: наука и практика, 2020)
Objective: to identify skiers individual respiratory system characteristics depending on their physical condition. Materials and methods: the study involved 20 professional skiers (10 men and 10 women, aged 23.2±0.9) who performed a long-term aerobic test (treadmill and bicycle ergometer) and a short-term anaerobic physical test (Wingate test on a bicycle ergometer). The gender and age specifi c data was processed and analyzed with generally accepted statistical methods. Before and after exercise, each subject underwent the individual respiratory system frequency characteristics and lung vital and forced vital capacity measurement to evaluate the physical activity effect on the respiratory system volume and frequency characteristics. The mean values in the reference groups and their standard deviations were calculated. Results: an analysis of the respiratory system frequency characteristics after physical exercise revealed a signifi cant change in resonance in men only in the exhalation phase after the “to failure” bicycle ergometric test, and in women only in the inhalation phase after treadmill test, all other frequency characteristics changes were insignifi cant. The maximum change in lung vital and forced vital capacity was found in men after treadmill stress test. The minimum change in lung vital and forced vital capacity was found in the male athletes after the “to failure” bicycle ergometer test. A signifi cant change in the resonant frequencies was found in the group of men only at the exhalation phase after “to failure” bicycle ergometer test., in women – only at the inhalation phase after the treadmill test. Conclusions: thus, the study revealed that both prolonged aerobic exercise and short anaerobic exercise do not result in signifi cant changes in the athletes’ respiratory system frequency characteristics suggesting the great potential of respiratory system bio-acoustic stimulation in sports medicine, since it can be performed at any period of the competitive training process at the time convenient for an athlete.